2021
DOI: 10.1042/cs20210971
|View full text |Cite
|
Sign up to set email alerts
|

AT2R stimulation with C21 prevents arterial stiffening and endothelial dysfunction in the abdominal aorta from mice fed a high-fat diet

Abstract: The aim of this study was to evaluate the effect of Compound 21 (C21), a selective AT2R agonist, on the prevention of endothelial dysfunction, extracellular matrix (ECM) remodeling and arterial stiffness associated with diet-induced obesity (DIO).  5-week-old male C57BL/6J mice were fed a standard (Chow) or high-fat diet (HF) for 6 weeks. Half of the animals of each group were simultaneously treated with C21 (1mg/kg/day, in the drinking water), generating 4 groups: Chow C, Chow C21, HF C, HF C21. Vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
2
6
0
Order By: Relevance
“…It is important to note that studies of our group have previously revealed vascular alterations, including endothelial dysfunction and a defective NO release, in mice fed a HF diet for 6 weeks. [17][18][19] The main findings of this study are that restoring a healthy diet for a period as short as 2 weeks after HF diet intake was enough to reduce BW and improve metabolic parameters, endothelial function, and AMPKderived vascular responses in the thoracic aorta, due to the activation of the AMPK/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is important to note that studies of our group have previously revealed vascular alterations, including endothelial dysfunction and a defective NO release, in mice fed a HF diet for 6 weeks. [17][18][19] The main findings of this study are that restoring a healthy diet for a period as short as 2 weeks after HF diet intake was enough to reduce BW and improve metabolic parameters, endothelial function, and AMPKderived vascular responses in the thoracic aorta, due to the activation of the AMPK/CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…Hypercaloric diets, including not only HF 7,[16][17][18][19] but also high sucrose 20,21 and high fructose 22,23 diets, have all been shown to induce metabolic and vascular alterations. Several strategies, including moderate CR 24,25 and more recently, IF 26,27 or even time-restricted eating 28 have emerged as effective interventions for BW loss and improved health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, brachial–ankle PWV values after weight regaining were independent of body weight, high-sensitivity C-reactive protein (hs-CRP), or insulin resistance changes [ 56 ]. However, it is still unknown what impacts a decrease in PWV value after weight reduction the most; whether it depends on changes in adipokines and inflammatory markers or is due to weight reduction per se [ 57 , 58 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…In our model, C21‐mediated activation of iBAT in HFD‐fed mice did not modify body mass, but successfully reduced circulating insulin levels. In addition, previous reports from our group in these animals showed that C21 preserves the endothelial function in thoracic and abdominal aorta from obese mice, 26,27 demonstrating a role in cardiovascular protection. According to our results, C21 enhances BAT activity in obese mice by (i) enhancing thermogenesis via ETC and UCP1 upregulation; (ii) increasing BAT mass through a promotion of cell differentiation, and (iii) improving BAT function through a reduction in inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 59%
“…The vascular effects of this experimental approach have been previously reported in Gonz alez-Bl azquez et al 26,27 The experimental procedures were performed in accordance with the European Union Laboratory Animal Care Rules (86/609/ECC directive) and approved by the Ethical Committee of the San Pablo CEU University and the Animal Protection Area of the Comunidad Aut onoma de Madrid (PROEX 200/18).…”
Section: Animalsmentioning
confidence: 99%